DYNAMICS OF KNAPPING WITH BIPOLAR TECHNIQUES: MODELING TRANSITIONS AND THE IMPLICATIONS OF VARIABILITY. (November 2015) - Hiscock, Peter
Abstract : Bipolar techniques enable knappers to (i) fracture very small lithic cores, (ii) reduce cores to a smaller size than is convenient and efficient with freehand knapping techniques, and (iii) to remove relatively large flakes from those small cores. In this paper the capacity of bipolar percussion knapping to extend reduction is explored with a model relating the level of engineering difficulty to the rate of core abandonment. This model allows us to examine the process by which small cores worked in the hand begin to be flaked with a bipolar technique. The value of this model is illustrated with case studies from northern and southern Australia.